The Implementation of Water Purification Using Simple Tools - Khoirul Mardongan; Puput Sri Rahayu; Siti Hodijah; Dasmini Dasmini; Oktafia Fifi Adelia; Apria Linda Yanti (International Journal Labs, 2022)
Often there is rain causing a lot of water to overflow and mix with community well water, which provides murky well water. This study aims to describe how to clear water using a simple tool. To process raw water to be clean in the countryside requires a simple water filter. The people of Rokan Hulu consume water from dug wells. The condition of the well water is murky and easily polluted with surface water around it there are many ponds, sewers, small reservoirs, and rivers. People need to be given knowledge about clean water and how to process it. PGSD STKIP Rokania students practice clearing water using simple tools. The benefits of this research are expected as input in community efforts in clearing water.